1997
DOI: 10.1111/1523-1747.ep12292708
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of KSHV/HHV-8 in Mycosis Fungoides or Associated Disorders

Abstract: The recently discovered human virus known as Kaposi's sarcoma-associated herpesvirus (KSHV) or human herpesvirus-8 (HHV-8) has been associated with body-cavity-based lymphomas in AIDS patients. It is most closely related to two other herpesviruses, the Epstein-Barr virus and herpesvirus saimiri, which are known to be associated with lymphomas in humans and nonhuman primates, respectively. To determine whether KSHV/HHV-8 is involved in the pathogenesis of mycosis fungoides (MF) and related disorders, we used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…4 These results were not confirmed in following studies, suggesting that HHV-8 is not directly implicated in the pathogenesis of either cutaneous T-cell or B-cell lymphoma. [9][10][11] Results of our serologic study confirm the absence of any direct or indirect role of HHV-8 in the pathogenesis of lymphoproliferative disorders of the skin.…”
Section: Commentsupporting
confidence: 63%
See 1 more Smart Citation
“…4 These results were not confirmed in following studies, suggesting that HHV-8 is not directly implicated in the pathogenesis of either cutaneous T-cell or B-cell lymphoma. [9][10][11] Results of our serologic study confirm the absence of any direct or indirect role of HHV-8 in the pathogenesis of lymphoproliferative disorders of the skin.…”
Section: Commentsupporting
confidence: 63%
“…The immunofluorescence assay was performed as previously described. 10 Briefly, BCP-1 cells were fixed in 4% paraformaldehyde, rendered permeable with detergent (0.2% Triton ϫ 100, SigmaAldrich, Dorset, England), incubated with human sera (1:100) for 30 minutes at room temperature, washed in a combined solution of phosphate-buffered saline and 3% fetal calf serum, incubated for 30 minutes with anti-human IgG-fluorescein isothiocyanate conjugate (Dako, Carpinteria, Calif), and then washed again and examined using fluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Zucker-Franklin et al (31) reported the release of retroviral particles from cultured lymphocytes of 18 MF patients. However, to date, there is no convincing evidence for an involvement of either human T-cell Lymphotropic Virus Type-I nor human Herpesvirus 8 in the pathogenesis of MF (32,33). Patients with HL show defects in cellmediated immunity that can precede the development of the disease (34).…”
Section: Discussionmentioning
confidence: 99%
“…4 Some years ago, several studies provided strong evidence against a role for HHV-8 in the pathogenesis of mycosis fungoides (MF), the most common subtype of cutaneous T-cell lymphoma (CTCL). 5,6 In the October 2005 issue of the Archives, Trento and colleagues 7 investigated the prevalence of HHV-8 infection in an Italian population of 22 patients with lymphoproliferative diseases such as largeplaque parapsoriasis (LPP) and MF. Lesional skin samples, plasma, and peripheral blood mononuclear cells were analyzed for the presence of HHV-8.…”
mentioning
confidence: 99%